KEEFEKTIFAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTU MEDIA JANGTOR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV MI TARBIYATUL BANIN PERKALONGAN KABUPATEN PATI - Asykar Luthfan Alaika (Jurnal Guru Kita PGSD, 2018)
Abstract: Effectiveness of Jangtor Media Think Pair Share Learning Model onthe Ability to Solve Mathematical Problems in Grade IV Students of MITarbiyatul Banin Pekalongan Pati Regency. The purpose of this study was todetermine the effectiveness of the think pair share learning model assisted by themedia in improving students' mathematical problem solving skills in FPB and KPKmaterial. This type of research is to use the Pre Experimental Design that is used isthe One Group Pretest-Posttest Design. The study population was all MI TarbiyatulBanin Pekalongan students in the academic year 2017/2018. The sample taken was32 fourth grade students. The data in this study were obtained through observation,interviews, tests, and documentation. The results of the study obtained the averagepretest of 40.62 and the posttest average of 77.34. The results of the problem solvingcompleteness test analysis of students showed reaching KKM (70). So it can beconcluded that the media-assisted tps model is effective for improving mathematicalproblem-solving skills of fourth grade students at MI Tarbiyatul Banin PekalonganPati Regency.Keyword : Think Pair Share, Jangtor Media, Problem Solving CapabilitiesAbstrak : Keefektifan Model Pembelajaran Think Pair Share Berbantu MediaJangtor Terhadap Kemampuan Pemecahan Masalah Matematika Siswa KelasIV MI Tarbiyatul Banin Pekalongan Kabupaten Pati. Tujuan dalam penelitianini adalah untuk mengetahui efektifitas model pembelajaran think pair shareberbantu media jangtor dalam meningkatkan kemampuan pemecahan masalahmatematika siswa pada materi FPB dan KPK. Jenis penelitian ini adalahmenggunakan Pre Experimental Desaign yang digunakan adalah One Group Pretest-Posttest Desaign. Populasi penelitian adalah seluruh siswa MI Tarbiyatul BaninPekalongan tahun pelajaran 2017/2018. Sampel yang diambil adalah 32 siswa kelasIV. Data dalam penelitian ini diperoleh melalui observasi, wawancara, tes, dandokumentasi. Hasil penelitian diperoleh rata-rata pretest 40,62 dan rata-rata posttest77,34. Hasil analisis tes ketuntasan pemecahan masalah siswa menunjukkanmencapai KKM (70). Jadi dapat disimpulkan bahwa model tps berbantu mediajangtor efektif untuk meningkatkan kemampuan pemecahan masalah matematikasiswa kelas IV MI Tarbiyatul Banin Pekalongan Kabupaten Pati.Kata Kunci : Think Pair Share, Media Jangtor, Kemampuan Pemecahan Masalah